Geometric calibration of Colour and Stereo Surface Imaging System of ESA's Trace Gas Orbiter. Issue 1 (1st January 2018) - Tulyakov, Stepan; Ivanov, Anton; Thomas, Nicolas; Roloff, Victoria; Pommerol, Antoine; Cremonese, Gabriele; Weigel, Thomas; Fleuret, Francois
Highlights: A general method for geometric calibration of telescopes with off-axis optics is proposed. The method is successfully applied for calibration of CaSSIS on-board of ESA's ExoMars TGO. The method is shown to improve quality of the scientific products. Abstract: There are many geometric calibration methods for "standard" cameras. These methods, however, cannot be used for the calibration of telescopes with large focal lengths and complex off-axis optics. Moreover, specialized calibration methods for the telescopes are scarce in literature. We describe the calibration method that we developed for the Colour and Stereo Surface Imaging System (CaSSIS) telescope, on board of the ExoMars Trace Gas Orbiter (TGO). Although our method is described in the context of CaSSIS, with camera-specific experiments, it is general and can be applied to other telescopes. We further encourage re-use of the proposed method by making our calibration code and data available on-line.